Modelling and Numerical Simulation of the in Vivo Mechanical Response of the Ascending Aortic Aneurysm in Marfan Syndrome - Garcia-Herrera, C (Springer Verlag, 2017)
Marfan syndrome (MFS) is a genetic disorder that affects connective tissue, impairing cardiovascular structures and function, such as heart valves and aorta. Thus, patients with Marfan disease have a higher risk of developing circulatory problems associated with mitral and aortic valves prolapse, manifested as dilated aorta and aortic aneurysm. However, little is known about the biomechanical characteristics of these structures affected with MFS. This study presents the modelling and simulation of the mechanical response of human ascending aortic aneurysms in MFS under in vivo conditions with intraluminal pressures within normotensive and hypertensive ranges. We obtained ascending aortic segments from five adults with MFS subjected to a vascular prosthesis implantation replacing an aortic aneurysm. We characterised the arterial samples via ex vivo tensile test measurements that enable fitting the material parameters of a hyperelastic isotropic constitutive model. Then, these material parameters were used in a numerical simulation of an ascending aortic aneurysm subjected to in vivo normotensive and hypertensive conditions. In addition, we assessed different constraints related to the movement of the aortic root. Overall, our results provide not only a realistic description of the mechanical behaviour of the vessel, but also useful data about stress/stretch-based criteria to predict vascular rupture. This knowledge may be included in the clinical assessment to determine risk and indicate surgical intervention. © 2016, International Federation for Medical and Biological Engineering.